The Meaning of Kîšôr (Prov 31:19) - Wolters, Albert M. (Hebrew Union College annual, 1995)
The noun kîšôr in Prov 31:19 is a hapax legomenon of unknown meaning. Today it is usually translated 'distaff' (following Luther), but this is only one of many guesses that have been made in the history of interpretation. Similar uncertainty prevails with respect to the etymology of the word. Previous discussions have failed to take into account two relevant factors which help to delimit the meaning of kîšôr: the extremely tightly-knit literary structure of its immediate context, and the history of spinning. The artful construction of Prov 31:19—20, which functions as the literary pivot of the Song of the Valiant Woman, shows that kîšôr must be a virtual synonym of pelek 'spindle.' The history of spinning shows that the distaff was not used in the ancient Near East, and that the kîšôr, which is grasped with two hands, was most probably a doubling spindle (like Arabic mubram). The technique used in handling the kîšôr can be plausibly reconstructed on the basis of Egyptian and Palestinian archeological evidence. Finally, the etymology of the word can be most plausibly traced to Canaanite kṯr.